Analysis of the Application of Islamic Business Ethics Principles on Putat Jaya Market Traders Sale and Purchase Transactions in Surabaya - Sabilatul Khoiroh (Values: Jurnal Kajian Islam Multidisiplin, 2024)
The market serves as a mechanism to provide incentives and facilitate economic activities in the society, in particular the UMKM market in Indonesia, which is divided into two, modern market and traditional market. In this modern era, traditional markets are still in the public; although some are already interested in e-commerce, one of the markets still in demand by the population is the traditional market Putat Jaya that exists in Surabaya. Based on the phenomenon that occurred in the Putat Jay market, the author is interested in carrying out research with the title “Analysis of the application of Islamic business ethics in the sale and purchase transactions of fish traders in Putat Jaya Market in Surabaya City." In this study, the author uses qualitative methodology of a descriptive approach by performing three stages of data collection, namely observation, interviews, and documentation. Based on the results of research, on the Putat Jaya market, most traders have adhered to Islamic Shariah in sale and purchase transactions and have implemented some of the principles of Islamic business ethics.